Risk factors of developmental delay: a community-based study - Mei Neni Sitaresmi; Djauhar Ismail; Abdul Wahab (Indonesian Pediatric Society Publishing House, 2016)
Background Developmental delay is a common problem in children. Early detection of this disorders is mandatory in order to provide early interventions. Identification of the risk factors is important for strategic intervention. Objective To identify risk factors of developmental delay in children under five years old. Metlwds A community-based study of developmental screening was conducted, in Bambanglipuro, Bantul district, Province of Yogyakarta, between September and October 2007. Developmental screening was performed using a Kuesioner Pra Skrining Perkembangan (KPSP). Results Out of 632 children aged 3 to 60 months, 407 (64%) had normal development, 81 (28%) doubtful and 43 (8%) suspected developmental delay. A number of factors identified as the risk of suspected developmental delay were undernourished (OR 2.3, 95%CI 1.1 ; 4.8) , low birth weight (OR 2.6, 95%CI 1.1 ; 6.1), low educational level of mother (O R 2.5, 95%CI 1.3; 4.9) , working mother (O R 1.8, 95%CI 1; 3.5), and poor socio-economic status (SES) families (OR 2.7, 95%CI 1.3; 5.4). Multivariate logistic regression analysis showed that poor SES was the strongest risk factor of suspected developmental delay (adjusted OR 2.8, 95%CI 1.4;5.7) . Conclusions Poverty, low maternal educational level and intrauterine malnutrition during as well as malnutrition during infant period are risk factors of developmental delay. Integrated strategies should be conducted to solve the problems to prevent more children suferred from developmental delay.